Testing the Associations between Coping, Mental Health, and Satisfaction with Life in Portuguese Workers - Filipe Rodrigues; Pedro Morouço; Tiago Santos (MDPI AG, 2023)
The present study aimed to explore the relationships between coping strategies, symptoms of depression, anxiety, and stress, and satisfaction with life among Portuguese workers. A sample of 402 participants (207 male, 195 female), ranging in age from 18 to 70 years (M = 32.90, SD = 11.75), was included in the study. Participants reported varying levels of work experience, ranging from 1 to 45 years (M = 10.62, SD = 4.07). The sample encompassed diverse occupations, including arts and design (n = 28), engineering (n = 23), marketing (n = 27), administration (n = 50), transportation and logistics (n = 57), clerks (n = 63), lawyers (n = 21), factory workers (n = 20), accountant and finance (n = 41), journalism (n = 27), health care (n = 29), and others (n = 16). To examine the associations between each determinant and satisfaction with life, hierarchical multiple regression analyses were conducted. Two models were tested, with predictors entered in blocks based on theoretical and empirical considerations. The second model accounted for 52.4% of the variance in satisfaction with life (F (14, 384) = 3.884, p < 0.001, R2 = 0.27, adjusted R2 = 0.24). Depressive symptoms and stress consistently exhibited a significant association (p < 0.05) with satisfaction with life across all tested models. In terms of coping mechanisms, instrumental support reinterpretation, disengagement, and humor demonstrated a significant association with satisfaction with life (p < 0.05). The findings suggest that employing adaptive coping strategies may help mitigate symptoms of mental distress and enhance satisfaction with life. By understanding the relationships between coping strategies, mental health symptoms, and satisfaction with life, interventions can be developed to promote well-being and improve overall quality of life among Portuguese workers.